2009
DOI: 10.1152/ajpendo.91001.2008
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of GH-releasing hormone and GH-releasing peptide synergy in men

Abstract: Veldhuis JD, Bowers CY. Determinants of GH-releasing hormone and GH-releasing peptide synergy in men. Am J Physiol Endocrinol Metab 296: E1085-E1092, 2009. First published February 24, 2009 doi:10.1152/ajpendo.91001.2008.-Age, sex steroids, and abdominalvisceral fat (AVF) jointly affect pulsatile growth hormone (GH) secretion. Pulsatile GH secretion in turn is controlled by GH-releasing hormone (GHRH), GH-releasing peptide (GHRP), and somatostatin. Marked stimulation of pulsatile GH secretion is achieved via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
1
5
0
3
Order By: Relevance
“…Twenty-four healthy young men [age 24 ± 0.72 (SEM) yr, BMI 25 ± 0.91 kg/m 2 ] received 2 consecutive im injections of depot leuprolide acetate (3.75 mg im 3 wk apart) to deplete systemic T and E 2 concentrations. The synergy between GHRH and GHRP-2 in these subjects was presented earlier (16). Beginning on the day of the second leuprolide injection, volunteers were given either saline (N = 13) or a pharmacological dose of 200 mg T enanthate (N = 11) im weekly for 3 doses (designated as days 0, 7, and 14) double-blind.…”
Section: Methodssupporting
confidence: 68%
See 1 more Smart Citation
“…Twenty-four healthy young men [age 24 ± 0.72 (SEM) yr, BMI 25 ± 0.91 kg/m 2 ] received 2 consecutive im injections of depot leuprolide acetate (3.75 mg im 3 wk apart) to deplete systemic T and E 2 concentrations. The synergy between GHRH and GHRP-2 in these subjects was presented earlier (16). Beginning on the day of the second leuprolide injection, volunteers were given either saline (N = 13) or a pharmacological dose of 200 mg T enanthate (N = 11) im weekly for 3 doses (designated as days 0, 7, and 14) double-blind.…”
Section: Methodssupporting
confidence: 68%
“…As described earlier and in a Supplemental (Appendix) Table, baseline subject characteristics did not differ in volunteers assigned to the leuprolide/placebo (Pl) and leuprolide/T treatment groups (16). In contrast, post-leuprolide vs post-placebo hormone concentrations differed significantly with respect to: (a) IGFBP-1 (higher in the T addback group, P = 0.027); (b) prolactin (higher in the T group, P = 0.001); (c) FSH (lower in the T group, P < 0.001); and (d) E 2 , total T, bioavailable T and free T (each higher by P < 0.001 in the T group): Figure 1 .…”
Section: Resultsmentioning
confidence: 80%
“…This pattern is attributed to the age-related decline in growth hormone secretion [33]. The complex interaction between sex steroids and GH-IGF axis is little known [39]. Nevertheless, physiologically, there is a positive association between androgens and IGF-I, and the contrary for estrogens [18].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, other unknown hepatic or non-hepatic mechanisms may be involved (such as genetic polymorphisms related to xenobiotic-metabolizing enzymes). In any case, the gender-and age-related differences observed may be linked to differences in interaction between sex steroid hormones and the GH/IGF system during infancy, pubertal transition, and adolescence [39].…”
Section: Discussionmentioning
confidence: 99%
“…In a result, his BMI was further increased. Therefore, he might have a visceral obesity, which may influence GH response to GHRP-2 [23]. The CT determination showed that he had no dominant of fat area in the abdomen compared with the subcutaneous tissue.…”
Section: Discussionmentioning
confidence: 99%